The Rejected Stone - Balogun, Lekan (Literamed Publications Nigeria Ltd, 2005)
The Rejected Stone is a play filled with lucid representations. Igbayiola is repudiated by her stepmother and stepsisters. She receives succour from Olokun, who brings about a positive turn in her destiny. She is later considered suitable to marry Prince Oranmiyan, after successfully passing through the 'sandal test'.
Keywords: Family; Drama; Mystery